2015
DOI: 10.3171/2014.12.jns142100
|View full text |Cite
|
Sign up to set email alerts
|

Spreading of multiple Listeria monocytogenes abscesses via central nervous system fiber tracts: case report

Abstract: Animal studies have shown that Listeria monocytogenes can probably access the brain through a peripheral intraneural route, and it has been suggested that a similar process may occur in humans. However, thus far, its spreading through the central nervous system (CNS) has not been completely elucidated. The authors present a case of multiple L. monocytogenes cerebral abscesses characterized by a pattern of distribution that suggested spread along white matter fiber tracts and reviewed the literature to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 34 publications
2
16
0
Order By: Relevance
“…A recent animal study suggests that once the bacteria have gained access to the CNS via the peripheral nervous system, the infection can spread along the axons, producing additional lesions by traveling within the axons of the trigeminal nerve [ 14 16 ]. According to Bojanowski et al, once inside the CNS, the bacterium may travel along the white fiber tracts of the brain, resulting in a distinct anatomical imaging thus enabling early diagnosis [ 17 ]. The spreading of multiple listeria brain abscess within the cerebral nervous system through the intrassonal pathway justified their specific pattern and why they have more detrimental effects than bacterial brain abscess.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent animal study suggests that once the bacteria have gained access to the CNS via the peripheral nervous system, the infection can spread along the axons, producing additional lesions by traveling within the axons of the trigeminal nerve [ 14 16 ]. According to Bojanowski et al, once inside the CNS, the bacterium may travel along the white fiber tracts of the brain, resulting in a distinct anatomical imaging thus enabling early diagnosis [ 17 ]. The spreading of multiple listeria brain abscess within the cerebral nervous system through the intrassonal pathway justified their specific pattern and why they have more detrimental effects than bacterial brain abscess.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, only 73 cases of brain abscess caused by L. monocytogenes were reported in the literature between 1968 and 2017. We report further two cases ( Table 1 ) [ 1 , 13 , 17 , 21 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A specific feature that pathologically differentiates this type of meningitis is the frequent involvement of brain parenchyma (including brain abscesses) and hematogenic dissemination [ 32 ]. Evidence for multiple abscesses along interconnected projection areas of the brain implies a possibility for distribution via white matter fiber tracts [ 33 ]. LLO is known to be critical for the development of listerial disease: LLO is required to release bacteria from the endosomal compartment in host cells, and toxin deficiency renders bacteria highly non-virulent [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…3,6,8,9 Our case exquisitely depicts a less well-recognised feature of listerosis brain abscesses, namely the propensity for the bacteria to spread to distant sites within the CNS utilising white-matter fibre tracts as conduits. 4 A recent literature review by Bojanowski et al. found that eight of the nine reported cases of supratentorial cerebral listeria abscesses followed a white-matter tract pattern of dissemination, and the majority of cases were limited to a single cerebral hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…13 There are few reported cases of L. monocytogenes cerebral infection spreading along white-matter fibre tracts, and a paucity of evidence documenting the serial imaging appearance following antimicrobial treatment. 4 We present a unique case of L. monocytogenes cerebral abscesses with intracerebral spread via the subcortical U-fibres and the extreme capsule, and review the microbiological literature to discuss mechanisms of bacterial mobility which may account for these neuroimaging findings.…”
Section: Introductionmentioning
confidence: 99%